Robert Pelletier : les histoires intrigantes et sans paroles d’un curieux reliquaire - Campeau, Michel; Carrière, Bertrand (CV Photo)

(untitled) (Les Productions Ciel variable, 1999)
Summary The multi-paneled, serial works in Curiosité - Le chercheur de trésor were the last made by Robert Pelleter before his death. They were conceived from the débris of civilization, and many of them are enigmatic. With the intention of exaggerating the magnificence of rejected objects, he photographed their shape, their shades, and the deposits of sediments that covered them in a warm, brilliant light, bringing out many details that were invisible to the naked eye.The authors discuss the idea that the artist, beyond his aesthetic infatuation with these vestiges, brought out the feeling of an experience born of sleep through the metaphoric device of image-objects. They refer to the thoughts of psychoanalyst Serge Tisseron, for whom objects are fundamentally extensions of our minds, images are also objects, and it is up to the individual to decide whether an object has something to say to him or her.